Why Does Doxycycline Pose a Relatively Low Risk for Promotion of Clostridioides difficile Infection? - Dongyan Xu; Thriveen Mana; Jennifer Cadnum; Abhishek Deshpande; Faezeh Afsari; Naseer Sangwan; Curtis Donskey (Case Western Reserve University, 2022)
Background:  Clinical studies suggest that doxycycline poses a low risk for promotion of Clostridioides difficileinfection, but the microbiologic explanation for this finding is unclear.  Methods:  Mice treated with oral doxycycline, oral azithromycin, subcutaneous ceftriaxone, doxycycline plus ceftriaxone, or azithromycin plus ceftriaxone were challenged with 104 colony-forming units of 2 different C. difficilestrains on day 2 of 5 of treatment. The concentration of C. difficile was measured in stool 2 and 5 days after challenge. The impact of the treatments on the microbiota was assessed by sequencing.  Results:  Doxycycline and azithromycin treatment did not promote colonization by either C. difficile strain in comparison to saline controls. Doxycycline treatment significantly reduced ceftriaxone-induced overgrowth of a C. difficile strain with doxycycline minimum-inhibitory concentration (MIC) of 0.06 µg/mL (P<0.01) but not a strain with doxycycline MIC of 48 µg/mL (P>0.05); azithromycin treatment did not reduce ceftriaxone-induced overgrowth of either strain. 16S rRNA amplicon sequencing revealed significantly lower bacterial diversity in the stool of ceftriaxone-treated mice, in comparison to doxycycline-treated and azithromycin-treated mice. Conclusions:  These findings suggest that doxycycline may have a low propensity to promote C. difficile colonization because it causes relatively limited alteration of the indigenous microbiota that provide colonization resistance and because it provides inhibitory activity against some C. difficile strains.